Discovery of the first apterous pincer wasp from amber, with description of a new tribe, genus and species of Apodryininae (Hymenoptera, Dryinidae) - Olmi, Massimo; Guglielmino, Adalgisa; Vasilenko, Dmitry V.; Perkovsky, Evgeny E. (Zootaxa, 2022)
†Rovnodryinus khomychi new genus and new species is described from Upper Eocene Rovno amber (Ukraine). It is the first apterous pincer wasp found in amber. This new taxon is attributed to the subfamily Apodryininae and the new tribe Rovnodryinini. The key to the subfamilies and tribes of Dryinidae is modified to include the new tribe. The new genus, known by a female, is characterized by the mesosoma almost completely composed of fused sclerites, the absence of wings and the presence of ocelli in the anterior half of the face. A close relationship of the new genus with the extant Apodryininae is underlined. R. khomychi is the first apodryinine found in the Northern Hemisphere. The tribe Rovnodryinini is the first higher taxon known only from Rovno amber. †Tritophania patruelis Jacobi and the tribe Elicini (Hemiptera, Fulgoromorpha, Tropiduchidae) are reported from Rovno amber for the first time.